Ideopolis di wilayah Bandaraya Kuala Lumpur: ke arah memperkasakan daya saing hub pendidikan di peringkat global (Ideopolis in the City-region of Kuala Lumpur: empowering an educational hub for global competitiveness) - Hamzah Jusoh; Habibah Ahmad; Noor Alyani Nor Azazi (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
The paradigm shift toward the k-economy in this era of globalization requires various stakeholders - industrialists, governance, universities - to be competitive, proactive and innovative in creating new ventures. To meet these demands, the formation of an ideopolis as a development strategy has become a central concern in developing countries. Various studies have shown that for an educational city-hub to function effectively as an ideopolis nine key components or drivers will need to emerge, namely, physical investment; building on existing assets; diverse specialization; high skill organisation; a vibrant education sector; a distinctive knowledge niche; connectivity leveraging; strong visionary leadership; and community investment. For Malaysia the question if it is meeting all the nine requirements of an ideopolis is relevant, crucial and needs to be answered. Based on an empirical case study of the Kuala Lumpur city-region, this paper seeks to gauge the extent to which the city-region has been able to meet some of those prerequisites. It concludes that the Kuala Lumpur city-region is an emergant ideopolis that sets to enhance the country’s regional and global competitiveness .